Cerebral Blood Flow Volume Using Color Duplex Sonography in Patients With Fibromyalgia Syndrome - Arzu KAYA; Gürkan AKGÖL; Arif GÜLKESEN; Ahmet Kürşad POYRAZ; Tülay YILDIRIM; Murad ATMACA (Archives of Rheumatology, 2018)
Objectives: This study aims to evaluate cerebral blood flow using color duplex Doppler ultrasonography in patients with fibromyalgia syndrome (FMS). Patients and methods: The study included 30 female patients with FMS (mean age 42.3 years; range 22 to 59 years) and 30 female healthy controls (mean age 39.6 years; range 22 to 56 years). Color duplex Doppler ultrasonography imaging was performed with an EPIQ 5 unit equipped with a multi-frequency linear probe (3-12 MHz) in the supine position. Severity of pain, fatigue, and the patient’s and physician’s global assessments of disease were evaluated on a visual analog scale. The Symptom Severity Scale, Hamilton Anxiety Rating Scale, Hamilton Depression Evaluation Scale, and Fibromyalgia Impact Questionnaire were also implemented to assess disease severity. Results: Cerebral blood flow volume and bilateral internal carotid artery (ICA) and vertebral artery (VA) volumes were not significantly higher in FMS patients compared to controls. Bilateral ICA and VA diameters were similar between FMS patients and controls. Bilateral mean peak systolic velocities and end diastolic velocities in the common carotid arteries, ICAs and VAs were similar in both groups. A significant correlation between symptom severity parameter and the cerebral blood flow volume was noted in FMS patients. Conclusion: Cerebral blood flow volume, ICA flow, and VA flow do not appear to increase, and are correlated with only Symptom Severity Scale among other clinical parameters reflecting disease severity in patients with FMS.